2019
DOI: 10.1111/nan.12570
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoural immune cell landscape in germinoma reveals multipotent lineages and exhibits prognostic significance

Abstract: Aims Alterations in microenvironments are a hallmark of cancer, and these alterations in germinomas are of particular significance. Germinoma, the most common subtype of central nervous system germ cell tumours, often exhibits massive immune cell infiltration intermingled with tumour cells. The role of these immune cells in germinoma, however, remains unknown. Methods We investigated the cellular constituents of immune microenvironments and their clinical impacts on prognosis in 100 germinoma cases. Results Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 36 publications
2
19
1
Order By: Relevance
“…Distinguishing the in ltration of TILs is critical for deconstructing the immunosuppressive microenvironment. Accumulating evidence indicates that TILs, which represent the local immune response [50][51][52], in many malignant tumors are related to the recurrence of several cancers [53][54][55]. Our research also con rmed that several immune biomarkers (CD3 + , CD8 + , CD45RO + ) were signi cantly associated with recurrence (S14 Fig) . However, this has a strong relationship with the location of TILs, and TILs at the IM seem to show more signi cant differences.…”
Section: Discussionsupporting
confidence: 72%
“…Distinguishing the in ltration of TILs is critical for deconstructing the immunosuppressive microenvironment. Accumulating evidence indicates that TILs, which represent the local immune response [50][51][52], in many malignant tumors are related to the recurrence of several cancers [53][54][55]. Our research also con rmed that several immune biomarkers (CD3 + , CD8 + , CD45RO + ) were signi cantly associated with recurrence (S14 Fig) . However, this has a strong relationship with the location of TILs, and TILs at the IM seem to show more signi cant differences.…”
Section: Discussionsupporting
confidence: 72%
“…Although these immune cells are mostly lymphocytes, especially B and T lymphocytes, other types of immune cells also exist in the interstitial space of germinoma. 6 , 7 It is yet to be investigated whether these immune cells play an antitumor role or merely coexist with tumor cells. 8 In seminoma, a testicular counterpart of germinoma, it has been reported that the abundance of tumor-infiltrating lymphocytes (TILs) has a prognostic significance.…”
mentioning
confidence: 99%
“… 9 Whereas in germinomas, we previously reported that tumor cell content may be associated with patient prognosis as well. 7 It was recently found that patients with germinoma at atypical sites (basal ganglia, cerebral hemisphere, cerebellum, or brainstem) were associated with worse prognosis compared with those at typical sites (neurohypophysis and pineal gland). 10 At present, it is yet to be clarified which clinical factors (tumor location and tumor cell content) have a bigger impact on the prognosis of germinoma.…”
mentioning
confidence: 99%
“…A small study of 8 patients with intracranial germinoma showed in all patients PD-L1 staining of the tumour cells and PD-1 expression of the tumour-infiltrating lymphocytes (TILs) and found a correlation between the immunosuppressive microenvironment and the growth of the tumours [ 101 ]. Takami et al evaluated the tumour immune microenvironment in 32 germinoma cases, concluding that tumour cells have a 73.5% positivity for PD-L1, while the majority of infiltrating, stained immune cells are PD-1 positive (93.8%), making germinomas a proper candidate for immunotherapy [ 102 ]. The high expression of CD4 T helper lymphocytes correlates with a good prognosis, while great levels of nitric oxide synthase 2 produced by myeloid-derived suppressor cells and macrophages associates with a shorter progression free survival (PFS), possibly by generating immune tolerance [ 102 ].…”
Section: Immunological Approachmentioning
confidence: 99%
“…Takami et al evaluated the tumour immune microenvironment in 32 germinoma cases, concluding that tumour cells have a 73.5% positivity for PD-L1, while the majority of infiltrating, stained immune cells are PD-1 positive (93.8%), making germinomas a proper candidate for immunotherapy [ 102 ]. The high expression of CD4 T helper lymphocytes correlates with a good prognosis, while great levels of nitric oxide synthase 2 produced by myeloid-derived suppressor cells and macrophages associates with a shorter progression free survival (PFS), possibly by generating immune tolerance [ 102 ]. Although there are some discrepancies between studies ( Table 7 ), the role of PD-1/PD-L1 pathway in germinomas warrants further investigation and may offer new potential therapeutic perspectives.…”
Section: Immunological Approachmentioning
confidence: 99%